Socio-spatial relations between violence and urban segregation: the case of Salvador de Bahía, Brazil - Ferreira da Costa, Thiago Augusto (2022)
Salvador de Bahia is the fourth largest and the most violent among Brazilian capital cities in rate of homicide (2021). However, the highest rates fall on the young and black man, residents in popular neighborhoods. The study's locus was the Atlantic Coast which, although it’s not the region of the city with the highest homicide rates, it’s dynamic in real estate market and contiguity between popular and high-income neighborhoods, showing the process of urban segregation and differences in public safety. In this way, the statistics of lethal violence (homicides and police actions) were analyzed in 2018-2020, to find relations with the socio-spatial and racial inequalities. For this, it was necessary to study socioeconomic indicators, as well as to map and to tabulate the deaths. The hot points and empty areas, in approximation, suggested to investigate micro-relationships and, with this, to problematize the nexus between violence and “poverty” as never absolute.